Effect of Salicylic acid on the antioxidant enzymes activity for callus of grape Vitis vinifera L. Halawini under salt stress - AL- KHAYAT, Baqer S.M. (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment aimed to study the effect of adding Salicylic acid in salinity stress on callus of grape Vitis vinifera L. Halawini. It was achieved in the laboratories of plant tissue culture belong to Horticulture and leaned scabe faculty of agriculture, University of kufa. during a period from October 2017 to December 2017. 250 mg of grape callus Halawini cultured under the effect of salicity stress in culture medium MS with sodium chloride (NaCl) (0, 75 and 150 mM) respectively with the adding salicylic acid(SA) on contractions (0, 0.5 and 1 mM). The culturing period was 8 weeks. The results revealed a significant effect for salicylic acid adding in lowering oxidative stress enzymes namely superoxide dismutase (SOD), catalase (CAT), Ascorbate peroxidas (APX) and peroxidase (POD).